Pengaruh Senam Defansi terhadap Penurunan Tekanan Darah dan Kemandirian pada Lansia - Diana Pefbrianti; Devi Hairina Lstari; M Noor Ifansyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Introduction. : Hypertension occurs in the elderly due to high intake of fat, sodium, smoking, lack of exercise, low sleep quality, and lack of physical activity. Prevention can be done by doing regular physical activity, reducing weight, diet management, limiting sodium, calcium and magnesium diets, reading healthy food labels, reducing stress and gymnastics. The purpose of this study was to see the effect of defansi exercise on blood pressure and independence of the elderly Methods: The research design in this study used experimental quasy design with pre and post control group design. The samples in this study were taken by consecutive sampling method as many as 25 respondents per group at PPRSLU Budi Sejahtera Banjarbaru. The independent variable in this study was defansi gymnastics, while the dependent variables were blood pressure and independence of the elderly. Data were analyzed through paired t tests. Results: The results showed that there was a significant difference in the results of blood pressure measurements before and after defansi gymnastics was given in the intervention group, namely p = 0.000 (p < 0.05), while in the control group there was no significant difference in the results of blood pressure measurements before and after. With p= 0.203 (p > 0.05). In the independence variable, there was no effect of defansi gymnastics on independence in both the intervention group p = 0.075 (p > 0.05) and the control group p = 0.948 (p > 0.05). Conclusion: There was an effect of defansi exercise on blood pressure in the intervention group, no effect of defansi exercise on blood pressure in the control group, and no effect of defansi exercise on independence in the intervention group and control group